2019
DOI: 10.1155/2019/1650145
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Antihyperglycemic Studies, and Docking Simulations of Benzimidazole-Thiazolidinedione Hybrids

Abstract: A simple and cheap three-step procedure for the synthesis of three (5Z)-5-[3(4)-(1H-benzimidazol-2-ylmethoxy)benzylidene]-1,3-thiazolidine-2,4-diones has been described via a SN2 reaction of generally recognized as safe hydroxybenzaldehydes and 2-(chloromethyl)-1H-benzimidazole, followed by a Knoevenagel condensation with thiazolidine-2,4-dione in moderated yields. All the newly synthesized compounds were characterized using analytical and spectral studies. In vitro treatment on adipocytes with compounds incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…A mixture of ortho-phenylene diamine (1.0 g, 9.25 mmol) and chloroacetic acid (1.32 g, 13.97 mmol) in 4 N HCl (60 mL) was refluxed for 24 h. The purified product was obtained by re-crystallization from water after neutralization with 6 N NH 4 OH, yield 0.4 g (40%). The product was used in the following step without further purification [ 63 ]. M.p.…”
Section: Methodsmentioning
confidence: 99%
“…A mixture of ortho-phenylene diamine (1.0 g, 9.25 mmol) and chloroacetic acid (1.32 g, 13.97 mmol) in 4 N HCl (60 mL) was refluxed for 24 h. The purified product was obtained by re-crystallization from water after neutralization with 6 N NH 4 OH, yield 0.4 g (40%). The product was used in the following step without further purification [ 63 ]. M.p.…”
Section: Methodsmentioning
confidence: 99%
“…We performed this assay according to a previous methodology that was used in our lab [5,37]. Briefly, the animals were fasted for 8 h, after which the groups (n = 6) were administered a 100 mg/kg dose of the different treatments, in addition to one vehicle group (10% Tween 80) and one positive control group (20 mg/kg glibenclamide).…”
Section: Acute Antidiabetic Assaymentioning
confidence: 99%
“…These receptors are found in diverse tissues. Through the activation of PPAR-γ, thiazolidinediones (TZDs, also known as glitazones) modify the transcription of genes that encode for factors involved in the intake of glucose (e.g., GLUT-4 [5,6]) and in the metabolism of glucose and fatty acids [4,7]. Accordingly, they promote the sensitization of tissues to insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding TZDs that serve as PPAR-γ agonists (Figure 1), the structure contains an acid region (a TZD ring acting as the pharmacophore), an aromatic center, and a cyclic polar/nonpolar region or hydrophobic side chain [5][6][7][8][9][10]. Due to the relatively large ligandbinding pocket (1200 Å 3 ) of the receptor [4,7], numerous chemical modifications have been proposed to construct glitazone derivatives, generating great structural diversity [5][6][7][8][9][10]. Several authors have suggested that the presence of a double bond in carbon 5 of glitazone derivatives is a favorable characteristic [5][6][7][8]11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation